The effect of correcting VerifyNow P2Y12 assay results for hematocrit in patients undergoing percutaneous coronary interventions. (25th February 2017) - Janssen, P. W. A.; Bergmeijer, T. O.; Godschalk, T. C.; Le, T. T. D.; Breet, N. J.; Kelder, J. C.; Hackeng, C.M.; Ten Berg, J. M.
Abstract : Essentials Platelet reactivity is correlated with thrombotic risk after percutaneous coronary intervention (PCI). Hematocrit (HCT) is associated with platelet reactivity as measured with the VerifyNow P2Y12 assay. We tested a formula proposed to correct VerifyNow measurements for HCT in 978 PCI patients. Correcting platelet reactivity for HCT did not improve the prediction of thrombotic events after PCI. Summary: Background: High on‐treatment platelet reactivity is predictive for the occurrence of atherothrombotic events following percutaneous coronary interventions (PCIs). A low hematocrit (HCT) value is associated with higher platelet reactivity values, expressed in P2Y12 reaction units (PRU), as measured with the VerifyNow P2Y12 assay. However, it is suggested that this is only an in vitro phenomenon. Objective: To determine whether adjusting PRU for HCT improves the predictive value for thrombotic events following PCI. Material and methods: The VerifyNow P2Y12 assay was performed in clopidogrel‐treated patients undergoing non‐urgent PCI included in a prospective cohort study. PRU values were corrected for HCT with a formula proposed in recent literature. Receiver operating characteristic (ROC) curves were made to determine the optimal cut‐off values to predict the occurrence of the primary endpoint, a composite of all‐cause death and non‐fatal myocardial infarction, stent thrombosis and ischemic stroke, during 1 year of follow‐up. The chi‐squared test was performed to determine whether correcting PRU for HCT improved the prediction of the primary endpoint. Results: A total of 978 patients were analyzed. A negative correlation between PRU and HCT was observed ( R 2 = 0.104). The optimal cut‐off value for the corrected PRU was 215. ROC analyses showed that prediction of the primary endpoint did not differ for the corrected PRU (area under the curve, 0.61; sensitivity, 0.57; specificity, 0.64) and the uncorrected PRU (area under the curve, 0.61; sensitivity, 0.69; specificity, 0.53). Conclusion: Correcting PRU for HCT does not improve the prediction of thrombotic events following PCI.